Analysis of a constrained forgetting factor recursive least squares algorithm in system identification - Carrette, P. (Proceedings of 35th IEEE Conference on Decision and Control, 1996)
In this paper, we deal with deterministic dominance of stochastic equations. The obtained results lead to the evaluation of tight upper-bounds upon the parameter tracking error of the forgetting factor recursive least squares (RLS) algorithm applied to the identification of time-varying systems.